Ontology of Factors Determining Website Value - Ordysiński, Tomasz (Ontologia czynników determinujących wartość serwisu internetowego, 2011)
Dynamic development of e-business creates many Internet initiatives, the market value of which is sometimes enormous (e.g. Google, E-bay, Amazon or Allegro). Such high results of market pricing are not consistent with the present methods of company pricing. The conclusion is then that there must be considered new factors determining website’s value, which should be applied in more accurate pricing methods. The attention of this article is focused on classification of bases of pricing methods, in the form of identification and description of factors determining the value of Internet site. Due to complexity and multidimensionality of that problem the ontological attitude is proposed. There is built a prototype of ontology of website’s value factors, which enables more “natural” mapping of real world phenomenon.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 187, s. 244-256
Keywords: ontologia; serwis internetowy; witryny internetowe; World Wide Web (www); website; internet websites